Safety of Early Carotid Endarterectomy after Intravenous Thrombolysis in Acute Ischemic Stroke - Gunka, Igor; Krajickova, Dagmar; Lesko, Michal; Renc, Ondrej; Raupach, Jan; Jiska, Stanislav; Lojik, Miroslav; Chovanec, Vendelin; Maly, Radovan (Annals of vascular surgery, 2017)
BACKGROUND: The timing of carotid endarterectomy (CEA) after intravenous thrombolysis (IVT) is still a controversial issue. The aim of this study was to assess the safety of early carotid interventions in patients treated with thrombolysis for acute ischemic stroke. METHODS: A retrospective analysis was performed using prospectively collected data from consecutive patients who underwent CEA for symptomatic internal carotid artery stenosis within 14 days after the index neurological event during the period from January 2013 to July 2016. Patients who had undergone IVT before CEA were identified. The primary outcome measures were any stroke and death rate at 30 days, symptomatic intracerebral hemorrhage and surgical site bleeding requiring intervention. RESULTS: A total of 93 patients were included for the final analysis. Among these, 13 (14.0%) patients had undergone IVT before CEA while 80 (86.0%) patients had CEA only. The median time interval between IVT and CEA was 2 days (range: 0-13). A subgroup of 6 patients underwent CEA within 24 hours of administration of IVT. The 30-day combined stroke and death rate was 7.7% (1 of 13) among patients undergoing IVT before CEA and 5.0% (4 of 80) among those undergoing CEA only (P = 0.690). In the IVT group, there were no cerebral hemorrhages or significant surgical site bleeding events requiring reintervention. CONCLUSIONS: Our experience indicates that CEA performed early after IVT for acute ischemic stroke, aiming not only to reduce the risk of stroke recurrence but also to achieve neurological improvement by reperfusion of the ischemic penumbra, may be safe and can lead to favorable outcomes.
Keywords: karotická endarterektomie; Female; nemoci arterie carotis; Thrombolytic Therapy; Administration, Intravenous; výsledek terapie; ženské pohlaví; intravenózní podání; cévní mozková příhoda; Registries; Time Factors; časové faktory; trombolytická terapie; lidé; Stroke; Treatment Outcome; Aged, 80 and over; ischemie mozku; Risk Factors; retrospektivní studie; Male; fibrinolytika; Aged; Carotid Artery Diseases; Endarterectomy, Carotid; Brain Ischemia; rizikové faktory; Time-to-Treatment; čas zasáhnout při rozvinutí nemoci; lidé středního věku; registrace; senioři nad 80 let; senioři; mužské pohlaví; Fibrinolytic Agents; Retrospective Studies; Middle Aged; Humans